2021
DOI: 10.11591/ijere.v10i2.20726
|View full text |Cite
|
Sign up to set email alerts
|

School space selection preferences: Architectural perspective toward formal school

Abstract: <span lang="EN-US">School space plays an essential role in creating a pleasurable learning atmosphere. The tendency of everyone to choose a school space also varies. By knowing this trend pattern, schools can be designed to improve student learning effectiveness. The purpose of this study was to find out which school spaces students choose to study, what kind of room criteria are needed, and distribution patterns of students' preference choices. This research used both the qualitative exploratory and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While past studies have shown that the state of school facilities has an effect on students' academic success, healthy living, school selection choice, learning behavior, and psychomotor activities [2,4,5,8,10], The other important dimension that is often neglected is school security, and [43] observe that there are a relatively small number of scholars and practitioners who compile data in this area with limited opportunities for debate and discussion. Studies have shown that narrowly focusing on security has led many educational institutions to ignore some of the services and school conditions that are essential to academic achievement, student well-being, and school safety [44].…”
Section: Discussion Of Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…While past studies have shown that the state of school facilities has an effect on students' academic success, healthy living, school selection choice, learning behavior, and psychomotor activities [2,4,5,8,10], The other important dimension that is often neglected is school security, and [43] observe that there are a relatively small number of scholars and practitioners who compile data in this area with limited opportunities for debate and discussion. Studies have shown that narrowly focusing on security has led many educational institutions to ignore some of the services and school conditions that are essential to academic achievement, student well-being, and school safety [44].…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…As the world moves from an industrial age to a knowledge-driven economy, there is a need to develop new knowledge and improve human capital, especially in developing countries like Nigeria. In the literature, it has been established that the state of facilities and utilities in an academic institution affects students' preferences in selecting schools [1,2], their academic performance [3][4][5][6][7], their psychomotor learning [8,9], and their learning behaviors [10]. However, it is imperative to note that not all studies report a positive relationship between the state of school facilities and learning outcomes [5,11,12].…”
Section: Introductionmentioning
confidence: 99%